PENGEMBANGAN MEDIA ULAR TANGGA “AYO, MEMBACA!” UNTUK KETERAMPILAN MEMBACA PERMULAAN SISWA SD KELAS II - Simanjuntak Grace Octora; Kurniawati; S. Nailul Muna Aljamaliah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading skills are essential for everyone. Mastery of early reading skills will influence students’ grades and improve their learning at school. This study aims to: (1) Analyze students’ needs regarding early reading learning materials in second grade. (2) Design the “Let’s, Read Snakes and Ladders” learning media for early reading skills. (3) Develop the “Let’s, Read Snakes and Ladders” media in accordance with the stages of early reading. (4) Test the use of the “Let’s, Read Snakes and Ladders” media on the early reading skills of second-grade students. This study used the D&D method with the stages of analysis, design, development, testing, and evaluation. In the development of the Snakes and Ladders media, it will undergo a validation process by 2 content experts and 2 media experts. The results of the subject matter expert validation achieved a 100% rating in the “Highly Acceptable” category. Then, the results of the media expert validation achieved ratings of 75% and 100%, which, when averaged, resulted in a 75% rating in the “Acceptable” category. Based on these results, the “Let’s, Read” snakes-and-ladders game is suitable for testing with second-grade students. In addition, there were also results from teacher and student questionnaires. Keywords: Early reading, Instructional media, Syllables, Media development,Indonesian language. ABSTRAK Kemampuan membaca permulaan menjadi hal penting yang harus dimiliki setiapmanusia. Penguasaan pada kemampuan membaca permulaan merupakan hal yang akan mempengaruhi nilai dan peningkatkan belajar siswa di sekolah. Penelitian ini bertujuan untuk: (1) Menganalisis kebutuhan siswa terhadap media pembelajaran membaca permulaan di Kelas II. (2) Mendesain rancangan media ular tangga “Ayo, Membaca!” untuk keterampilan membaca permulaan. (3) Mengembangkan media ular tangga “Ayo, Membaca!” sesuai dengan tahapan membaca permulaan. (4) Menguji penggunaan media ular tangga “Ayo, Membaca!” terhadap keterampilan membaca permulaan siswa Kelas II. Penelitian ini menggunakan metode D&D dengan tahapan analisis, perancangan, pengembangan, uji coba, dan evaluasi. Pada pengembangan media ular tangga, akan melalui proses validasi dari 2 ahli materi dan 2 ahli media. Hasil dari validasi ahli materi mendapatkan presentase 100% dengan kategori “Sangat layak”. Kemudian, hasil validasi ahli media mendapatkan presentase 75% dan 100% yang jika di rata-rata kan menjadi 75% dengan kategori “Layak”. Melalui hasil tersebut, media ular tangga “Ayo, Membaca!” layak untuk diuji cobakan pada siswa Kelas II. Selain itu, terdapat juga hasil kuesioner guru dan siswa. Kata Kunci: Membaca permulaan, Media pembelajaran, Suku kata, Pengembanganmedia, Bahasa Indonesia.